D Python Language Reference - Bassi, Sebastian (Python for Bioinformatics, 2010)
This text is based on Richard Gruet’s “Python Quick Reference.” It is included here by permission of the author. This work is also available online at http://rgruet.free.fr/PQR25/PQR2.5.html. The online version is under a Creative Commons Attribution-Noncommercial-Share Alike 2.0 license. For more information on this license please see: http://creativecommons.org/ licenses/by-nc-sa/2.0/fr/deed.en_US.